Drug-induced fibrosing syndromes: A scoping review - Sakir Ahmed; Prasanta Padhan; Partisha Gupta (Indian Journal of Rheumatology)
There are numerous case reports implicating drugs in the pathogenesis of scleroderma-like fibrotic syndromes. A MEDLINE and SCOPUS search was made in an attempt to review these drugs. The entire spectrum of sclerodermatous disorders ranging from localized morphea, fasciitis, and linear scleroderma to the classical diffuse systemic sclerosis with typical autoantibody formation have been reported in association with drugs. Some drugs such as bleomycin and pentazocine have been established to cause fibrosis and are used to create animal models of systemic sclerosis. There are controversies regarding the role of others such as beta-blockers. Certain chemotherapeutic agents and ergot derivatives can also lead to fibrosing disorders. The new checkpoint inhibitors have been shown to develop systemic sclerosis like disease among other “immune related adverse effects.” The mechanisms leading to fibrosis are poorly understood in case of most drugs due to paucity of data. This limits therapeutic strategies. However, many of these syndromes regress if the causative drug is withdrawn early. Thus, it is imperative for clinicians to have knowledge about these syndromes and identify them early.